Correction to: Rosuvastatin-Loaded Glycerosomes as a Neuroprotective Strategy Against Hyperlipidemia-Induced Brain Dysfunction: Development, Optimization, and in vivo Evaluation - Mahran Mohamed Abd El-Emam; Mohamed Ibrahim; Milad Reda Qelliny; Mahmoud Mostafa; Marwa Mohamed El Sayed; Maha S. Kilany; Amira Ebrahim Alsemeh; Rania Said Moawad; Mohamed Fouad Mansour (Journal of Pharmaceutical Innovation, 2027)

Effect of using mannan-oligosaccharides and β-glucans as feed additives on growth, biochemical parameters, and immunity of Salmonella enterica serovar Enteritidis-challenged turkey - Shimaa A. Amer; Rehab I. Hamed; Gehan K. Saleh; Abdel-Wahab A. Abdel-Warith; Elsayed M. Younis; Ahmed Gouda; Rania M. Ibrahim; Nehal M. Nabil; Maram M. Tawakol; Momen M. Aladl; Walaa A. El-Sayed; Mohamed A. Mahmoud; et al. (Veterinary Research Communications, 2026)

Toxic effects of MPs and Up Grade® herbicide on the Nile tilapia (Oreochromis niloticus): Oxidative stress, immune responses, and histopathological investigations - Rashad E.M. Said; Ahmed E. A. Badrey; Mohamed Hamed; Ibrahim A. Mohamed; Hamdy A.M. Soliman; Alaa El-Din H. Sayed (Veterinary Research Communications, 2026)

Preparation and evaluation of a monovalent Foot and Mouth Disease vaccine as a rapid response to the emerging serotype SAT1 in Egypt - Sonia A. Rizk; Hany I. Abu-Elnaga; Hend M. Daoud; Wael Mossad; Ehab El-Sayed Ibrahim; Mohamed A. Gamil; Nermeen G. Shafik; Mohamed S. Abousenna; Samir A. Nassif; Mohamed A. Saad (Veterinary Immunology and Immunopathology, 2026)

Rosemary (Rosmarinus officinalis) Extract Attenuates Methotrexate-Induced Oxidative Stress, Inflammatory Disturbance, and Apoptotic Lung Injury: A Molecular and Histopathological Study - Abd El Ghany A. Moustafa; Aly Fahmy Mohamed; Ibrahim M. Ibrahim Amr; Hassan Fathy Kaabo; Laila El-sayed El-moselhy; Tamer Albasyoni Gomah; Amer M. Abdel Hamid; Amal Mahmoud Hammad; Walid Mostafa Sayed Ahmed; Fawzy Mahmoud Abou Galala; Fayez Mohammed Abd Elfattah Elbayoumy; Mohamed E. Amer; et al. (Cell Biochemistry and Biophysics, 2026)

Correction to: Repurposing doxycycline as an adjunct to sitagliptin in type 2 diabetes mellitus: a randomized controlled study on glycemic, inflammatory, and cardiometabolic outcomes - Eman El‐Khateeb; Mohannad O. Khrieba; Amal Mohammad Badawoud; Ahmed A. Morsy; Aya A. El‑Hanafy; Eman Hamza; Eslam Habba; Doaa A. El‑Hanafy; Nashwa Eltantawy; Reham A. Al‑Dhelaan; Kholoud H. Radwan; Abeer A. El‑Sayed; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Exploring the therapeutic potential of Lupeol isolated from Ochrosia elliptica Labill. leaves in polycystic ovarian syndrome - Essam Abdel-Sattar; Marwa A. Ibrahim; Fady Sayed Youssef; Marwa S. Khattab; Riham A. El-Shiekh; Rehab A. Ghandour; Shimaa R. Emam; Heba Hozyen; Marwa Zakaria; Samar M. Mouneir (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Hydroxyapatite nanoparticles improve vitrified bovine MII oocyte developmental competence by reducing ultrastructural damage and modulating gene expression - Xiao-Xia Li; Yi-Hang Wang; Jun Wang; Shi-Yu Zhang; Jia-Hao Zhang; Shi-Han Zhao; Qi Yan; Ping-Hua Cao; Zi-Qiang Zhang; Chen Zhou; Zhen Zhang; Qiao-Ting Shi; et al. (Animal Reproduction Science, 2026)

Repurposing doxycycline as an adjunct to sitagliptin in type 2 diabetes mellitus: a randomized controlled study on glycemic, inflammatory, and cardiometabolic outcomes - Eman El‐Khateeb; Mohannad O. Khrieba; Amal Mohammad Badawoud; Ahmed A. Morsy; Aya A. El-Hanafy; Eman Hamza; Eslam Habba; Doaa A. El-Hanafy; Nashwa Eltantawy; Reham A. Al-Dhelaan; Kholoud H. Radwan; Abeer A. El-Sayed; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Corrigendum to “Ecological risk assessment of selected contaminants in seawater, sediment and some fish species from Alexandria beaches, South-Eastern Mediterranean Sea, Egypt”. [Environ. Nanotechnol. Monit. Manage. 20 (2023) 100873] - Safaa A. Abdel Ghani; Mohamed I.A. Ibrahim; Mohamed A. Shreadah; Abeer A.M. El-Sayed; Mohamed A. Aly-Eldeen (Environmental Nanotechnology, Monitoring & Management, 2026)

Macromodeling and experimental investigation of RC frames infilled with clay bricks and autoclaved aerated concrete blocks under cyclic loading - Ahmed M. El-Kholy; Huda Sayed; Ibrahim M. Metwally; Ayman A. Shaheen (Bulletin of Earthquake Engineering, 2026)
This study investigates the cyclic behavior of reinforced concrete (RC) frames infilled with autoclaved aerated concrete (AAC) blocks—a novel and environmentally friendly material—compared to traditional clay masonry infill commonly used in Egypt. In addition, the RC frames were reinforced with an advanced type of reinforcing steel designed to enhance seismic resistance. Three 2/3-scale RC frames were experimentally tested under cyclic lateral loading. Both infill types contributed approximately equally to increasing the lateral strength of the RC frame (around 60% improvement); however, the AAC infill significantly outperformed the brittle clay infill in terms of ductility enhancement. To characterize the response, trilinear and quadlinear backbone curves were developed for the clay and AAC infills, respectively. Alongside the experimental work, numerical macromodeling of the infill panel as multi-strut and single-strut macromodels using SeismoStruct and SAP2000, respectively, was conducted. Additionally, both concentrated and distributed plasticity approaches were employed to model the nonlinear behavior of the RC elements. A suitable constitutive steel model was used to numerically track the experimental hysteresis response of the steel reinforcement. The multi-strut macromodel demonstrated superior accuracy in capturing the hysteresis behavior of the infilled RC frames compared to the single-strut model. The strut width and its post-cracking degradation rate, the shear-to-axial stiffness ratio, and the strain in the infill at peak stress were key parameters influencing the accuracy of the complex multi-strut macromodel in distinguishing between the brittle behavior of clay infill and the ductile response of AAC infill.

Effect of stinging nettle powder (Urtica dioica) supplementation on productive and physiological performance of laying hens - Magdy Sayed Hassan Hassan; Inas Ibrahim Ismail; Ahmed Mohamed Dief Youssef; Ahmed M. Hussein; Nahla A. Elrazik; Ibrahim Abd El hamed Fathy; EIham Salah Mohamed Ahmed; Waleed Sobhy El Saqa; José del Carmen Rodríguez-Castillo; Mona M. M. Y. Elghandour (Tropical Animal Health and Production, 2026)

Rosuvastatin-Loaded Glycerosomes as a Neuroprotective Strategy Against Hyperlipidemia-Induced Brain Dysfunction: Development, Optimization, and in vivo Evaluation - Mahran Mohamed Abd El-Emam; Mohamed Ibrahim; Milad Reda Qelliny; Mahmoud Mostafa; Marwa Mohamed El Sayed; Maha S. Kilany; Amira Ebrahim Alsemeh; Rania Said Moawad; Mohamed Fouad Mansour (Journal of Pharmaceutical Innovation, 2026)
Objective Brain injury and neurodegenerative conditions are largely caused by oxidative damage and endoplasmic reticulum (ER) stress spurred on by hyperlipidemia. To lessen these consequences in the brains of hyperlipidemic rats, this study assesses the therapeutic potential of both rosuvastatin glycerosomes (RSV GLSMs) and niacin. Methods The study had five groups: control, hyperlipidemia induced by poloxamer 407 (P407), RSV GLSMs, niacin, or a combination of RSV GLSMs and niacin. Serum samples were collected for lipid profile assessment, whereas brain tissues were harvested for Reverse Transcription Polymerase Chain Reaction, histopathological, and immunohistochemical analyses. Results The treatment of P407 significantly decreased high-density lipoprotein and increased serum triglycerides, although RSV GLSMs and niacin substantially mitigated these changes. Malondialdehyde also surged in P407 rats, and total antioxidant capacity was diminished. RSV GLSMs and niacin supplementation significantly improved antioxidative defenses, with the combination therapy exhibiting more pronounced effects. RSV GLSMs and niacin notably lessen ER stress–responsive gene expression, including Eukaryotic Initiation Factor 2 alpha (eIF2α), C/EBP Homologous Protein (CHOP), X-box Binding Protein 1 (XBP1), c-Jun N-terminal Kinase (JNK), Binding Immunoglobulin Protein (BIP), and Activating Transcription Factor 6 (ATF-6) levels. In addition, RSV GLSMs and niacin improved autophagy by downregulating the Mammalian Target of Rapamycin (mTOR) and p62, and upregulating Beclin1 and Microtubule-associated protein 1A/1B-light chain 3, type II (LC3-II). According to immunohistochemical findings, RSV GLSMs and niacin reduced reactive gliosis and modulated the expression of B-cell lymphoma 2/Bcl-2-associated X protein (Bcl-2/Bax). Histopathological findings exhibited improved brain morphology, reduced vacuolization, and normalized glial cell distribution in the RSV GLSMs and niacin combination group, closely resembling the control group. Conclusions Overall, RSV GLSMs and niacin effectively mitigate hyperlipidemia-induced brain damage by modulating oxidative stress, ER stress, and autophagy pathways, suggesting potential as a promising treatment strategy.

Ursolic acid, a pentacyclic triterpene from Ochrosia elliptica Labill leaves and its role in the management of polycystic ovary syndrome (PCOS) - Shimaa R. Emam; Marwa A. Ibrahim; Fady Sayed Youssef; Marwa S. Khattab; Riham A. El-Shiekh; Rehab A. Ghandour; Heba F. Hozyen; Marwa Zakaria; Essam A. Abdel-Sattar; Samar M. Mouneir (Inflammopharmacology, 2026)
Ursolic Acid (UA), a naturally occurring pentacyclic triterpene, was isolated from Ochrosia elliptica . Polycystic Ovary Syndrome (PCOS) a prevalent endocrine disorder characterized by hyperandrogenism, insulin resistance, and chronic inflammation. In this study, we investigate the role of UA in alleviating the symptoms of PCOS, focusing on its biochemical, hormonal, and histopathological effects in a rat model. Using adult female Wistar Albino rats, PCOS was induced through letrozole administration. The rats were then treated with UA at two different doses (25 and 50 mg/kg), alongside a control group and a standard ovulation-inducing medication, clomiphene citrate (1 mg/kg). Biochemical analyses showed that PCOS induction significantly increased serum malondialdehyde (MDA) levels by approximately 1.21-fold, while markedly reducing superoxide dismutase (SOD) and catalase (CAT) activities ( p ≤ 0.05) by approximately 0.48-fold, relative to negative control. Treatment with UA (50 mg/kg) dose-dependently restored oxidative balance, reducing MDA (~ 0.82-fold) and elevating SOD (~ 2.39-fold) and CAT (~ 2.11-fold) activities toward PCOS values ( p ≤ 0.05). Hormonally, PCOS rats exhibited elevated luteinizing hormone (LH) and testosterone levels by approximately 1.70-fold, compared to the negative control ( p ≤ 0.05). Both doses of UA significantly lowered LH and testosterone, with the 50 mg/kg dose achieving reductions comparable to clomiphene citrate ( p ≤ 0.05). Histopathological examination showed improved ovarian morphology with reduced cystic follicles and increased corpus lutea in UA-treated groups. Furthermore, UA downregulated key genes involved in steroidogenesis and oxidative stress response, suggesting a multifaceted mechanism of action. The findings highlight UA’s potential as a novel therapeutic option for managing PCOS symptoms, emphasizing the need for further research into its efficacy and safety in clinical applications.

Improving growth traits in rabbits: a comparative study of Gabali, New Zealand White, and their hybrids using 18S rDNA sequencing - Hairul Islam Mohamed Ibrahim; Abdullah Sheikh; Roshmon Thomas Mathew; Muhammad Munir; Gamal Bekhet; El-Sayed Hemdan Eissa; Sameh A. Abdelnour; Mohamed D. Mahran (Tropical Animal Health and Production, 2026)

Probiotics and Diet Modifications: A Holistic Approach to Tackling Helicobacter pylori with the Help of the Gut Microbiota - Tamer A. Addissouky; Yuliang Wang; Ibrahim El Tantawy El Sayed; Naser A. Naser; Mohammed Jalal AlAhmed (Probiotics and Antimicrobial Proteins, 2026)

Alogliptin repositioning confers protection against diclofenac-induced liver injury by inhibiting TLR4/NF-κB, ROS/TXNIP, and NLRP3 inflammasome-mediated pyroptosis in rats - Nermein F. El Sayed; Mohamed H. Noureldin; Ibrahim El Sayed; Yousra Y. El Banna; Mai El-Sayed Ghoneim (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Pimenta racemosa extract ameliorates chemically induced ulcerative colitis in rats by suppressing inflammation and oxidative stress - Haitham A. Ibrahim; Fathia S. Elshaarawy; Mohamed I. S. Abd-elhady; Wafaa Hamdy; Merhan E. Ali; Asmaa A. Ahmed; Elsayed K. El-Sayed (Inflammopharmacology, 2026)
Pimenta racemosa ( P. racemosa ) tree leaves are used in traditional medicine to alleviate flatulence and gastrointestinal disorders. Ulcerative colitis (UC) is a gastrointestinal inflammatory disease with well-known inflammatory and immunoregulatory pathological features. The complexity of the disease requires multi-targeted treatment. Because of their relative safety and effectiveness, natural products can be utilized as adjunct and alternative agents to conventional UC treatment. So , the present work aimed to isolate phenolic constituents of the plant’s 80% aqueous methanol extract (AME) and evaluate its protective effect on acetic acid-induced ulcerative colitis (UC) in rats. The defatted AME was chromatographed, and structures of the isolated compounds were elucidated using UV, NMR spectroscopy and HPLC–ESI–MS analysis. Induction of ulcerative colitis was done using Acetic acid, the protective effect against ulcerative colitis was supported by histopathological and immunohistochemical examinations. The isolated compounds are Kaempferol 3- O - β -D-glucopyranoside (kaempferol 3- O -glucoside) or (Astragalin) (1) , quercetin 3- O-β -D-glucopyranoside (Isoquercetrin) (2) , Quercetin (3) , Catechin (4) , quercetin 3- O-α- L-rhamnospyranoside (Quercetrin) (5) . The AME of P. racemosa significantly alleviated the UC by decreasing the disease activity index and Wallace score. Additionally, GSH, CAT, and SOD were increased, and MDA was decreased, suggesting AME’s antioxidant activity. The decreased levels of WBCs, neutrophils, TNF-α, IL-1β, IL-6, MPO, and NF-κB p65 support the AME’s anti-inflammatory properties. The highest activity was recorded for the dose of 1000 mg/kg. These findings were in harmony with the histopathological examination and the Alcian Blue staining for mucin content. The current study revealed that the AME of P. racemosa has protective activities against UC in rats via its antioxidant and anti-inflammatory properties may be attributed to its phenolic profile.

Thiamine-functionalized magnetic coffee-derived carbon for efficient methylene blue removal: Synthesis, mechanism, and performance evaluation - Abdullah M. Aldawsari; Hassan M.A. Hassan; Mosaed S. Alhumaimess; Ibrahim Hotan Alsohaimi; Ayoub Abdullah Alqadami; Mohammad S. Algamdi; Mohamed Y. El-Sayed (Journal of Environmental Chemical Engineering, 2026)

Nanocapsule-based vitamin B12 as a novel strategy against vancomycin-induced nephrotoxicity: Targeting oxidative stress, ER stress, inflammation, and fibrosis in rats - Mahran Mohamed Abd El-Emam; Maha S. Kilany; Mohamed Ibrahim; Milad Reda Qelliny; Mahmoud Mostafa; Marwa Mohamed El Sayed; Tarek khamis; Rasha Ahmed Ahmed Agaga; Asmaa Monir Eltaweel; Mohamed Fouad Mansour (Toxicology and Applied Pharmacology, 2026)

Cerium oxide nanoparticles attenuate hepatic failure via blocking TGF-β/Smads and upregulating Nrf2/HO-1 signaling pathways in liver fibrosis rat model - Noha A. Mowaad; Sara M. Baraka; Saber Ibrahim; Doaa A. Mansour; Reda M. S. Korany; Ahmed F. El-Sayed; Arwa A. Hassan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)
T his article is aimed at assessing the anti-fibrotic action of plant-based fabricated cerium oxide nanoparticles (CeO 2 NPs). The Carissa carandas aerial parts methanolic extract was utilized to prepare CeO 2 NPs, where the dispersal of particle size distribution and zeta potential value was 61.9 nm and − 18.94 mV, respectively, verifying the successful synthesis of CeO 2 NPs. In rats, CeO 2 NPs were intravenously injected at doses of 0.1 and 0.5 mg/kg twice a week for a month, in parallel with thioacetamide (TAA, 200 mg/kg, i.p). Our findings revealed that CeO 2 NPs alleviated the alteration in serum GPT, GOT, ALP, total bilirubin, albumin, and total protein levels induced by TAA. Additionally, the hepatic oxidative insult due to TAA was inferred by elevation in malondialdehyde and reduction of glutathione content, which in combination with downregulation of SIRT1, Nrf2, and HO-1 in hepatic tissues was improved by CeO 2 NPs. A clear repression in hepatic fibrosis was observed in CeO 2 NP-treated groups as demonstrated by significant downregulation in TGF-β1 and p-Smad 2 and 3 proteins and COL1A1, MMP-2, and α-SMA expressions in hepatic tissues. The histopathological outcomes exhibited a considerable accumulation of collagen fibers in hepatocytes in TAA-challenged rats, which was ameliorated by CeO 2 NPs. Also, CeO 2 NPs dampened the death of hepatic cells via blocking caspase 3 activation as indicated by the immunohistochemical results. The in silico investigations documented the powerful binding affinities of TGF-β1, COL1A1, MMP-2, p-Smad2, p-Smad3, SIRT1, Nrf2, and HO-1 proteins with CeO 2 NPs. In conclusion, this study emphasized the efficacy of CeO 2 NPs as a potent anti-fibrotic agent through upregulating SIRT1/Nrf2/HO-1 and downregulating TGF-β1/Smads pathways.

Development and characterization of BSA-pullulan gel matrices incorporating orange peel flavonoids: Structural interactions and antimicrobial and antioxidant functionalities - Mahmoud Salah; Mabrouk Sobhy; Yajing Fang; Salwa M. El-Sayed; Ibrahim Khalifa; Ali Korin; Mohammed Mansour; Syed Asim shah Bacha; Sajid Maqsood; Yun Wang (Food Chemistry, 2025)

Guar gum-based systems formulated with encapsulated propolis extract for minimally processed fruits and confectionery packaging - Rowaida K. Khalil; Nadeen B. El-Sayed; Rawan H. El-sayed; Rahma M. Sallam; Asmaa Y. Abdelnabi; Nouran S. Soliman; Rawan A. Ibrahim; Menna-tallah A. Ibrahim; Muhammed R. Sharaby; Dalia S. Abdelrahim (Food Hydrocolloids, 2025)

Paleoenvironmental setting and facies analysis of the Middle Miocene carbonate platform in north Western Desert, Egypt - Ibrahim M. Ied; Sherif Farouk; Sayed Abd El-Azeam; Mohammad Abd-Elazez; Ibtsam A. Abd EL-Rauf (Carbonates and Evaporites, 2025)
The Marmarica Formation in the north Western Desert (NWD) of Egypt is predominantly composed of Middle Miocene carbonate rocks. A detailed microfacies and paleoenvironmental analysis was conducted on six representative surface sections extending from the Siwa to Matruh areas: Dakrur, North Siwa (NS), Siwa-Matruh 1 (SM1), Siwa-Matruh 2 (SM2), Abu Khrait, and Agiba. Field observations and lithological data indicate that the Marmarica Formation can be subdivided into three informal members: lower, middle, and upper. A distinct facies shift is observed from interbedded shale and carbonate in the Siwa area to predominantly carbonate facies towards the north in the Siwa-Matruh and Matruh areas. Microfacies analysis of the studied sections identified twelve distinct microfacies types, which are grouped into three main facies associations, corresponding to three paleoenvironmental settings: restricted lagoonal platform interior, open marine shelf (platform top), and high-energy platform shoal. Based on the vertical and lateral distribution of these facies, a homoclinal ramp depositional model is proposed, revealing a clear deepening trend from south to north. In the southern Siwa area, the depositional system evolves vertically from a protected, restricted lagoon to open shelf and shoal settings. Towards the north, the environment becomes progressively deeper, dominated by fluctuations between open marine shelf and high-energy shoal environments. Sequence stratigraphic analysis identified three third-order transgressive-regressive (T-R) depositional sequences (SQ1, SQ2, SQ3), each comprising transgressive system tracts (TST) and highstand system tracts (HST) and are separated by two sequence boundaries (SB1 and SB2). These sequences correspond to global eustatic cycles—such as Haq et al. 1987 and Hardenbol et al. 1998- and correlate with equivalent Miocene carbonate systems in the Tethyan realm highlighting the interplay of eustatic sea-level changes and regional tectonics on carbonate platform evolution during the Langhian–Serravallian stages.

Corrigendum to “Rational design of chitosan/guar gum/zinc oxide bionanocomposites based on Roselle calyx extract for Ras cheese coating” [Carbohydr. Polym., Volume 239, 1 July 2020, 116,234] - Samah M. El-Sayed; Hoda S. El-Sayed; Osama A. Ibrahim; Ahmed M. Youssef (Carbohydrate Polymers, 2025)

Poly(styrene-alt-chitosan malonate)/poly(ether sulfone) blend membranes for ultrafiltration with enhanced antifouling performance - Mosaed S. Alhumaimess; Ibrahim Hotan Alsohaimi; Raghad Ayed Alenazi; Mohamed Y. El-Sayed; Abdullah M. Aldawsari; M.R. El-Aassar; Ahmed A. Alshahrani; Hassan M.A. Hassan (Journal of Water Process Engineering, 2025)

Phage therapy and its role in cancer treatment and control - Heba Ibrahim Abd El-Moaty; Ahmed S. Doghish; Hebatallah Ahmed Mohamed Moustafa; Wagiha S. Elkalla; Ghadir A. Sayed; Nourhan H. Elshami; Sherif S. Abdel Mageed; Osama A. Mohammed; Mahmoud A. Elrebehy; Kareem AlFarsi; Amr M. Abdelfatah; Aly M. Waseem; et al. (Folia Microbiologica, 2025)

Biological, biochemical, hormonal effect, and histological perturbations of Procambarus clarkii (Crustacea: Cambaridae) hemolymph on Biomphalaria alexandrina snails - Salwa A. H. Hamdi; Sayed Abd El-Monem; Amina M. Ibrahim; Mona F. Fol; Nesma A. Mostafa (Aquaculture International, 2025)
Schistosomiasis is a severe illness carried by snails of the genus Biomphalaria , which have a large distribution in Egypt. Control of the intermediate host snail is critical in limiting schistosomiasis spread. On the topic of snails’ management, bioactive products extracted from aquatic invertebrates have gained more interest. Here, for the first time, the current research intended to identify the bioactive compounds present in hemolymph collected from the freshwater crayfish Procambarus clarkii and to assess its molluscidal activity against Biomphalaria alexandrina snails. Results showed that following exposure to the sub-lethal concentrations (LC 10 34.9 and LC 25 42.8 mg/l) of hemolymph, a reduction in survival and reproductive rates of B. alexandrina was detected, as well as a substantial increase in transaminases (AST and ALT) activities, while a reduction in total protein and albumin levels. Also, levels of testosterone and 17β-estradiol hormones decreased compared to the control group. Histopathological examination of the digestive gland of treated B. alexandrina displayed a shrinkage of the tubules and an increase in the inter-tubular spaces, and also, degeneration in the oocytes and spermatocytes of the hermaphrodite glands with a loss of connective tissues between the acini was observed. Thus, based on these results, a new strategy should be developed for a better use of these agents in schistosomiasis control.

Sublethal effects of S-metolachlor and myclobutanil on behavior, antioxidants, and acetylcholinesterase in Oreochromis niloticus as an indigenous predatory fish on larvae of the mosquito, Culex pipiens - Neama S. Saeed; Sayed A. Ahmed; Ibrahim A. Mohamed; Alaa El-Din H. Sayed (International Journal of Tropical Insect Science, 2025)

Stage-wise monitoring of microplastics (MPs) in wastewater treatment plants (WWTPs): Abundances, characteristics, polymer types, and removal - Wenbo Kong; Mabkhoot Alsaiari; Mohammed Jalalah; Farid A. Harraz; Ibrahim M. Hegab; Maha Awjan Alreshidi; El-Sayed Salama (Process Safety and Environmental Protection, 2025)

Combining 3D Resistivity Modelling, Well Logging and Hydrochemical Mapping for Identification of Lithofacies and Aquifer Contamination Sources - Abdallah Ibrahim Ammar; Osman Ebrahem Hassan; Enas El-Sayed Hussein; Kamal Ali Kamal (Water, Air, & Soil Pollution, 2025)
Population expansion and industrial growth in some modern cities are currently changing the surrounding environmental especially due to the impact of human activities on soil properties and groundwater resources. To investigate this, the resistivity method and hydrochemical analysis were employed and applied to create a 3D visual model of the sediments and their physical and hydrogeological properties. They were also used to map the hydrochemical properties of groundwater with a focus on the water of the Quaternary aquifer and identify its contamination sources. Hence, a 3D resistivity model delineated the dry and saturated layers and the extent of the effect of contaminants within the aquifer. This model was supported by geological, hydrogeological and well logs data. This resistivity model confirmed the aquifer contamination by the leakage and movement of contaminants to the southeastern, eastern, and northeastern parts of the study area. In addition, hydrochemical analyses of groundwater were conducted. They confirmed the presence of significant changes in the major cations and anions and trace elements due to the leakage and movement of contaminants to the same direction as detected from resistivity modelling. Accordingly, this work provides accurate and consistent results for decision-makers to track and identify contaminants, their causes, their spread, concentrations, and impact on groundwater properties. Using this methodology, new strategies can be developed to conserve groundwater and utilize it to achieve sustainable development in this area and similar areas.

Relationship Between Grain Yield Response Index and Wheat Genotypes Adapted to Nitrogen–Deficient Environments - Yassmin T. M. Emam; Afafa M. Tolba; Yasser A. El-Gabry; Ibrahim M. El– Metwally; Hani Saber Saudy; Amany N. Sayed (Journal of Soil Science and Plant Nutrition, 2025)
Plant breeders of self-pollinated crops such as wheat often obtain huge number germplasms via hybridization programs. However, screening these germplasms to select the best ones, especially in terms of nitrogen (N) use efficiency, is not an easy task. Thus, the current study was designed to determine the significance of grain yield response index (GYRI) as a promising parameter versus the traditional agronomic traits to characterize the most efficient and responsive wheat genotypes to applied N. The study involved twenty bread wheat genotypes (six commercial varieties namely Sakha 94, Sakha 95, Giza 171, Gemmiza 12, Masr 1, Masr 2 and 14 new lines, numbered from 1 to 14). Over two seasons, the performances of these genotypes were monitored under three N levels: optimum N (192 kg N ha –1 , farmer practice), moderate deficit N (144 kg N ha –1 +biofertilizer) and high deficit N (96 kg N ha –1 +biofertilizer). The experiment was designed in split-plot and replicated thrice. Line 11 under optimum N or high deficit N and Line 4 under moderate deficit N in the first season as well as Line 14 under high deficit N in the second season had the earliest heading time. Under normal N application (192 kg N ha –1 ), Masr 1 in the first season and Gemmiza 12 in the second season had the widest flag leaf. Under moderate deficit N, Line 6 in the first season and Line 14 in the second one surpassed all other genotypes. Application of 144 kg N ha –1 +biofertilizer×Line 3 in the second season outperformed all other genotypes grown under the other N treatments. Line 9, Line 10, Line 13, Sakha 95 and Gemmiza 12 (under moderate deficit N) as well as Line 7, Line 8, Line 9, Line 13, Line 14, Gemmiza 12 and Masr 1 (under high deficit N) recorded the greatest values of grain yield in the first season. While, Sakha 95 and Line 9 were the marked genotypes for producing the maximum grain yield under moderate deficit N and high deficit N, respectively, in the second season. GYRI estimation exhibited that Line 11 and Sakha 95 in the first season and Sakha 95 and Masr 2 in the second one were the efficient and responsive genotypes for N applications. Obviously, GYRI as a breeding parameter can contribute greatly to resolving the conflict between crop traits in terms of distinguishing N-deficiency tolerant varieties. Herein, GYRI detected that Line 11, Sakha 95 and Masr 2 are considered promising germplasms to develop and improve wheat to tolerate low N supply. Further, the increased grain yield of some tested genotypes (i.e. Line 5, Line 6, Line 8, Line 9, Line 13, Line 14, Giza 171, Masr 1, Gemmiza 12) under deficit N than optimal N is an observation worthy of in-depth future investigation.

Promising role of dietary microalgae blend in alleviating the heat stress draw backs in broiler chickens: Impact on performance, meat antioxidants and fatty acids content and expression of heat shock protein and sirtuins related genes - Doaa Ibrahim; Mohamed Shawky; Asmaa EL- Sayed Kamel; Ahmed Abdelfattah-Hassan; Rahma Taha; Samah S. Khalil; Mohamed Tharwat Elabbasy; Asmaa T.Y. Kishawy (Journal of Thermal Biology, 2025)

Rutin-Loaded Nanocapsules Mitigate Vancomycin-Induced Hepatotoxicity: Development, Characterization, Optimization, and In Vivo Evaluation - Mohamed Ibrahim; Mohamed Fouad Mansour; Mahran Mohamed Abd El-Emam; Tarek khamis; Maha S. Kilany; Amira Ebrahim Alsemeh; Asmaa Monir Eltaweel; Milad Reda Qelliny; Mahmoud Mostafa; Marwa Mohamed El Sayed (Journal of Pharmaceutical Innovation, 2025)
Background Vancomycin (VCM)-induced hepatotoxicity is a significant clinical concern due to its association with oxidative stress, apoptosis, and inflammatory responses. This study investigated the formulation and potential preclinical application of rutin-loaded nanocapsules (RUT-NC) as a hepatoprotective agent against VCM-induced liver injury. Methods Hepatotoxicity was induced in rats through VCM administration, followed by oral treatment with RUT-NC. Liver function, oxidative stress markers, apoptotic proteins, lipid metabolism regulators, and inflammatory cytokines were subsequently evaluated. Results RUT-NC treatment significantly improved liver function parameters, attenuated oxidative stress, and modulated apoptotic pathways by downregulating the expression of p38 , p53 , caspase-8 , miR-122 , miR-7 , and beclin-1. Furthermore, RUT-NC restored lipid metabolism homeostasis by regulating the expression of PPAR-α, FASN, and SREBP-1. Notably, it exerted potent anti-inflammatory effects by suppressing NF-κB , TNF-α , IL-1β , IL-6 , IL-17 , and Gasdermin-D , thereby mitigating chronic liver inflammation. The pathological effects of VCM administration on hepatocytes were effectively counteracted by RUT-NC. Conclusion RUT-NC demonstrates promising hepatoprotective properties by enhancing antioxidant defenses, inhibiting apoptosis, regulating lipid metabolism, and reducing inflammation. These findings highlight its potential as a therapeutic intervention for drug-induced liver injury (DILI) and warrant further investigation for clinical application.

Impacts of PVC microplastic ingestion on Biomphalaria alexandrina: behavioral, physiological, and histological responses - Amina M. Ibrahim; Ahmed A. A. Hussein; Menna H. E. Morsy; El-Sayed Baz (Hydrobiologia, 2025)
Microplastic pollution has emerged to be a crucial environmental concern. Despite the growing body of research on microplastic ingestion in oceans and marine organisms, there is a knowledge gap concerning the effects of microplastic exposure on freshwater ecosystems, which support diverse communities of plants, animals, and microorganisms. The freshwater snail Biomphalaria alexandrina is a valuable model for dissecting the ecological impact of many pollutants in aquatic environments. This study aimed to investigate the impacts of ingesting microplastic particles on B. alexandrina , particularly focusing on polyvinyl chloride (PVC), widely used in plastic applications, piping, electrical, and vehicle equipment, which results in their frequent presence in ecosystems. A combination of behavioral, physiological, biochemical, and histological assessments revealed profound effects of microplastic ingestion by these mollusks. These effects include the accumulation of PVC particles in their intestines, a reduction in feeding behavior, decreases in survival and growth rates, disruptions in biochemical parameters, induction of oxidative stress, and histological damage to their digestive glands. Additionally, our data suggest that the adverse impacts are concentration-dependent, with higher PVC concentrations causing more severe harm. Our findings advance our understanding of the potential consequences of microplastic pollution in freshwater habitats and inform targeted mitigation strategies.

Neuroprotective activity of Colocasia esculenta (L.) Schott leaves against monosodium glutamate-induced excitotoxicity in rats: phytochemical and molecular docking study - Heba T. Khazaal; Elsayed K. El-Sayed; Yara E. Mansour; Reham R. Ibrahim; Mokhtar Bishr; Rabab A. El Dib; Hesham S. M. Soliman (Natural Product Research, 2025)

Metabolite profiling of Cucurbita pepo L. in relation to its potential to combat experimental trichinosis - Nashwa R. Mohamed; Seham S. El-Hawary; Fatema R. Saber; Ibrahim E. Sallam; Shaimaa H. El-Sayed (South African Journal of Botany, 2025)

Efficient Augmentation of Superparamagnetic Ferrite with Alum Sludge as a Sustainable Nanoadsorbent Matrix for Promoting Dye Removal: Preparation, Characterization and Application - Ahmed Hashem Mangood; Eman Shaban Salama; Ibrahim El Tantawy El Sayed; Mai Kamal Fouad; Maha Abdelbaset Tony (International Journal of Environmental Research, 2025)

In vitro propagation and assessment of genetic stability in Eriobotrya japonica (Thunb.) Lindl. as affected by zinc oxide nanoparticles (ZnO-NPs) - Heba El-Sayed Ghareb; Sabha Salman Mustafa; Shafik Darwish Ibrahim; Mohamed Reda Abd Alhady; Mahdia Farid Gabr (In Vitro Cellular & Developmental Biology - Plant, 2025)
Eriobotrya japonica (Thunb.) Lindl . is an evergreen tree that holds economic significance. It is cultivated for its fruits, leaves and ornamental properties. Its propagation by seeds and cuttings is inefficient due to high heterozygosity, lengthy juvenile phase and reproductive cycle. This study establishes a direct in vitro propagation technique for the plant from the mother tree. The impact of different zinc oxide nanoparticle (ZnO-NP) concentrations on E. japonica ’s in vitro propagation was assessed. Genetic stability of the micropropagated plantlets was also conducted using start codon targeted (SCoT) and sequence-related amplified polymorphism (SRAP) markers to evaluate the protocols’ efficiency. Successful shoot establishment involved 1.0 mg L −1 6-benzyladenine (BA) and 0.1 mg L −1 α-naphthaleneacetic acid (NAA) supplemented to Murashige and Skoog (MS) medium, yielding 80% growth induction, the highest shoot number (3.72) and length (4.84 cm). MS medium with 1.0 mg L −1 BA and 1.0 mg L −1 kinetin (Kin) achieved 95% multiplication and optimal shoot number (5.70). Adding 50.0 mg L −1 ZnO-NPs significantly influenced shoot formation, leading to 100% growth induction, highest shoot number (7.67) and highest shoot length (4.0 cm). Rooting using 1.5 mg L −1 indole-3-butyric acid (IBA) in half MS medium achieved 100% rooting response and 85% survival for post-greenhouse acclimatization. Genetic stability analysis showed low degree of polymorphism (3.3%) and high percentage of monomorphic bands (96.7%) between donor and micropropagated plants. Dice’s similarity coefficient displayed high similarity (0.992 to 1.000) between sub-cultured and mother plants. An effective method for in vitro propagation of E. japonica was successfully established. ZnO-NPs significantly influence shoot formation and facilitate the mass production of E. japonica plants with desired characteristics.

Assessing seawater intrusion impact on groundwater quality in El-Omayed aquifers, Mediterranean coast, Egypt using hydrogeochemical and chemometric analyses - Mohammed I.A. Ibrahim; Mohamed A. El-Sawy; Ahmed R. Elgendy; Hossam M. El-Sayed; Laila A. Mohamed; Mohamed A. Aly-Eldeen (Groundwater for Sustainable Development, 2025)

Optimizing dehydration and viscosity reduction in Egyptian heavy crude oil emulsions using eco-friendly demulsifiers - Ahmed Z. Ibrahim; El Sayed H. El tamany; Mostafa A.A. Mahmoud; Mokhtar Al-Abyadh; H.A. El Nagy (Fuel, 2025)

Structural and Energetic Insights into the Binding of L- and D-Arginine Analogs with Neuropilin-1 (NRP1): Molecular Docking, Molecular Dynamics and DFT Calculations - Mahmoud A. A. Ibrahim; Dina E. M. Mohamed; Khlood A. A. Abdeljawaad; Alaa H. M. Abdelrahman; Shaban R. M. Sayed; Mohamed A. El-Tayeb; Peter A. Sidhom; Paul W. Paré (Cell Biochemistry and Biophysics, 2025)

Paleobiodiversity, Paleobiogeography, and Paleoenvironments of the Middle–Upper Eocene Benthic Foraminifera in the Fayum Area, Western Desert, Egypt - Mostafa M. Sayed; Petra Heinz; Ibrahim M. Abd El-Gaied; Ramadan M. El-Kahawy; Dina M. Sayed; Yasser F. Salama; Mansour H. Al-Hashim; Michael Wagreich (Journal of Marine Science and Engineering, 2025)
The middle–upper Eocene successions of northwest Fayum, Egypt, provide a crucial archive for reconstructing paleoenvironmental conditions and paleobiogeographical patterns of the southern Tethys realm. Stratigraphically, the investigated section is subdivided into three rock units: the Gehannam Formation (Bartonian-Priabonian), the Birket Qarun Formation, and the Qasr El Sagha Formation (Priabonian). A total of 101 benthic foraminiferal taxa, representing 31 genera, 23 families, 13 superfamilies, and four suborders, were identified. The middle–late Eocene age is primarily determined by the co-occurrence of index spinose planktonic foraminifera (Acarinina spp., Morozovelloides spp., and Globigerinatheka semiinvoluta) and benthic foraminiferal assemblages, further supported by the presence of the nannofossil marker Chiasmolithus oamaruensis. Four local benthic biozones are identified and correlated with coeval zones in nearby areas. Quantitative analyses of benthic foraminiferal individuals, diversity indices, ecological parameters, and the benthic foraminiferal oxygen index (BFOI) reveal distinct environmental shifts. The rock unit occupied by the late middle Eocene assemblages is diversified and dominated by calcareous infaunal taxa (e.g., Bolivina spp., Fursenkoina spp., and Nonionella spp.), indicative of low-oxygen outer neritic conditions associated with elevated organic influx. In contrast, the late Eocene Birket Qarun and Qasr El Sagha showed an increase in epifaunal forms and reduced diversity, suggesting a transition to dysoxic-oxic conditions. Paleobiogeographical analysis indicates a strong affinity with the Tethyan realm, with potential faunal exchange through the Trans-Saharan Seaway. These findings enhance our understanding of Paleogene marine connections between the Tethyan and Indo-Pacific realms, contributing to broader discussions on Eocene paleobiogeography and depositional dynamics in North Africa.

Comparative Neuroprotective Potential of Nanoformulated and Free Resveratrol Against Cuprizone-Induced Demyelination in Rats - Sara A. M. El-Sayed; Ghadha Ibrahim Fouad; Maha Z. Rizk; Hanan H. Beherei; Mostafa Mabrouk (Molecular Neurobiology, 2025)
Demyelination is a frequent yet crippling neurological disease associated with multiple sclerosis (MS). The cuprizone (CZ) model, which causes demyelination through oxidative stress and neuroinflammation, is a popular tool used by researchers to examine this process. The polyphenol resveratrol (RESV) has become a promising neuroprotective agent in seeking for efficient therapies. In a rat model given CZ, we created and examined iron oxide nanoparticles (IONPs) loaded with RESV (IONP-RESV) to see how effective they were as a therapeutic agent against free RESV. According to molecular mechanisms, exposure to CZ resulted in a marked downregulation of myelin proteolipid protein (PLP) expression and an overexpression of the inflammatory markers tumor necrosis factor-α (TNF-α) and S100β, which are indicators of demyelination and neuroinflammation. It is remarkable that these CZ-induced alterations could be reversed by therapy with either RESV or IONP-RESV. Interestingly, IONP-RESV showed even stronger anti-inflammatory activity, as shown by a more noticeable downregulation of TNF-α and S100β expression. These results were confirmed by histopathological examination of the cerebral cortices. Our findings support the better neuroprotective benefits of RESV-loaded IONPs over free RESV in reducing demyelination and neuroinflammation brought on by CZ. Owing to their pro-remyelinating, anti-inflammatory, and antioxidant properties, RESV-loaded IONPs show promise as a neurotherapeutic intervention in the future for neurological diseases such as multiple sclerosis. Graphical Abstract

Physiological and Molecular Responses of Red Amaranth (Amaranthus cruentus L.) and Green Amaranth (Amaranthus hypochondriacus L.) to Salt Stress - Tartil M. Emam; Abd Elaziz M. Hosni; Ahmed Ismail; Ramy G. El-Kinany; Mohammed Hewidy; Hani Saber Saudy; Mohamed M. A. Omar; Mariam T. S. Ibrahim; Shunzhao Sui; Salwa M. El-Sayed (Journal of Soil Science and Plant Nutrition, 2025)
Salinization, as a serious climate change phenomenon, continues to cause critical issues for soils and crops. Abundance of genetic diversity of plants could contribute in solving the impacts of salinity. However, the relations between physiological and molecular traits of plant species need deep investigation and interpretation. Pot experiments were conducted in the greenhouse to investigate the difference in behavior between two amaranth species when they were beforehand subjected to salinity-stress conditions, specifically on some specific physiological and molecular characteristics. After 45 days from transplanting, salt stress was induced using a 150 mM sodium chloride solution. Treatments were arranged in randomized complete block design using three replications. After 0, 2, 6, 10, and 24 h, samples were collected to evaluate physiological data as well as diversity of gene expression. The samples were immediately frozen in liquid nitrogen and stored in -80⁰ C ultralow temperature refrigerators. Findings revealed that the red amaranth species ( Amaranthus cruentus ) was more tolerant to saline stress than the green amaranth species ( Amaranthus hypochondriacus ). Result data revealed that malondialdehyde (MDA) content in the red amaranth increased after 2 h then decreased (after 6 and 10 h) before rising again after 24 h. In the green amaranth, MDA content initially decreased after 2 h before increasing and later decreasing in a zigzag pattern ending in an increase after 24 h. There was an initial steep rise in proline content of green amaranth after 2 h which continued to still rise moderately till 24 h. In the red amaranth the initial rise in proline continued after 2, 6 and 10 h before it stopped. Results also showed that red amaranth gave higher value of superoxide dismutase (SOD) activity as compared with green amaranth in all tested salinity exposure times. The investigation on the expression of four genes assessed through quantitative PCR indicated the efficiency of red amaranth in increasing the expression of SOS1, HKT1, NHX1, and DGR2 genes, which encode adaptation-related proteins under salinity stress. In summary, the current work demonstrated that red amaranth could be an efficient genetic resource in improving salt-tolerant genotypes belonging to Amaranthus genus.

Enhancing the performance of rigid pavement slabs using sugarcane bagasse ash and macro synthetic fibers - Esraa Elsayed Elayouty; Shady Rezk Ragheb; Ahmed Mohammed Youssef; Marwa El-Sayed El-Bany; Ibrahim Saad Agwa (Innovative Infrastructure Solutions, 2025)
This study uses a few materials with various ratios, such as sugarcane bagasse ash (SBA) and macro synthetic fiber (MSF), to enhance the rigid pavement slab (RPS) load-carrying capacity (LCC). In the study presented herein, the investigation was developed in two phases. Firstly, we selected materials and evaluated their physical, mechanical, and chemical characteristics. Nine different concrete mixes were designed as part of the study. The investigation focused on the ratio of replacement SBA used, which ranged from 0 to 25% by weight of the cement content, and MSF ratios 0.5%, 1%, and 1.5% by volume of concrete mixture. Compressive strength (CS), flexural strength (FS), slump, and splitting tensile strength (STS) were used to assess each mixture’s characteristics. SEM was also used to illustrate the specifics of the SBA results. Accordingly, three mixes have been chosen to be used in the next. In the second phase, a study was conducted on the ultimate LCC for RPS internal, edge, and corner. Nine RPS measuring 800 mm × 800 mm × 50 mm were constructed and subjected to a static load at three different locations. The optimal ratios for high mechanical properties are 10% SBA replacement for cement content and 1% MSF inclusion by volume in the concrete mixture. The CS of SBA10 increases by approximately 7.32% compared to its reference mixture. With the SBA10F1 mix design, there is a 34% increase in ultimate LCC for internal loading, a 33% increase for edge loading, and a 36% increase for corner loading compared to its reference mixture. This research presents new insights into the combined use of SBA and MSF, contributing to the development of more sustainable RPS.

Neuroprotective effect of red dragon fruit extract ameliorates oxidative stress and inflammation in D-galactose-induced aging rat model: biochemical, histological and immunohistochemical study - Manar Fouli Gaber Ibrahim; Fatma F. Ali; Sayed Fouad El-Sheikh Ali; Emad S. Shaker; Hemdan I. Mahmoud; Fatma ElZahraa Mohammed Abdellatif; Sahar A. Mokhemer (Journal of Molecular Histology, 2025)

Foraminiferal biostratigraphy and depositional environment of the late Albian–Cenomanian Al Hilal formation in northeastern Libya - Ibrahim M. Abd El-Gaied; Yasser F. Salama; Mansour H. Al-Hashim; Michael M. Grammer; Sayed M. Abd El-Aziz (Carbonates and Evaporites, 2025)

Berberine-loaded iron oxide nanoparticles alleviate cuprizone-induced astrocytic reactivity in a rat model of multiple sclerosis - Ghadha Ibrahim Fouad; Mostafa Mabrouk; Sara A. M. El-Sayed; Mohamed F. Abdelhameed; Maha Z. Rizk; Hanan H. Beherei (BioMetals, 2025)
Berberine (BBN) is a naturally occurring alkaloid as a secondary metabolite in many plants and exhibits several benefits including neuroprotective activities. However, data on the neuromodulating potential of nanoformulated BBN are still lacking. In the present study, BBN loaded within iron oxide nanoparticles (BBN-IONP) were prepared and characterized by transmission electron microscopy FTIR, X-ray photoelectron spectroscopy particle-size distribution, zeta potential, and HPLC. The remyelinating neuroprotective potential of BBN-IONP relative to free BBN was evaluated against cuprizone (CPZ)-induced neurotoxicity (rats administered 0.2% CPZ powder (w/w) for five weeks). CPZ rats were treated with either free BBN or IONP-BBN (50 mg/kg/day, orally) for 14 days. Cognitive function was estimated using Y-maze. Biochemically, total antioxidant capacity lipid peroxides and reduced glutathione in the brain tissue, as well as, serum interferon-gamma levels were estimated. Moreover, the genetic expression contents of myelin basic protein Matrix metallopeptidase-9 Tumor necrosis factor-α (TNF-α), and S100β were measured. The histopathological patterns and immunohistochemical assessment of Glial Fibrillary Acidic Protein in both cerebral cortex and hippocampus CA1 regions were investigated. CPZ-rats treated with either free BBN or IONP-BBN demonstrated memory restoring, anti-oxidative, anti-inflammatory, anti-astrocytic, and remyelinating activities. Comparing free BBN with IONP-BBN revealed that the latter altered the neuromodulating activities of BBN, showing superior neuroprotective activities of IONP-BBN relative to BBN. In conclusion, both forms of BBN possess neuroprotective potential. However, the use of IONPs for brain delivery and the safety of these nano-based forms need further investigation.

Biosorbent silver nanoparticles decorated coffee-ground waste composite for cleaning water and antimicrobial applications - Azza A. Al-Ghamdi; Sherif M. Ibrahim; Xingmei Lu; Jiayu Xin; Ibrahim El-Tantawy El-Sayed; Ahmed A. Galhoum; Swelm. Wageh (Environmental Science and Pollution Research, 2025)

In vivo antischistosomal activity profiling and efficacy of niosomal Spirulina platensis and praziquantel combined remedy against murine Schistosoma mansoni infection - Heba Abdel-Tawab; Shrouk E. Al-Sayed; Fatma I. Abo El-Ela; Amina M. Ibrahim; Olfat A. Hammam; Almahy M. El-Mallah (Veterinary Parasitology, 2025)

Correction to: The effects of nano‑selenium and/or vitamin C on the growth performance, blood health, organ histology, molecular alterations, and disease resistance of Nile tilapia (Oreochromis niloticus) against Saprolegnia ferax - Hayat Ali Alafari; Najah M. Albaqami; Yasmin M. Abd El‑Aziz; Yasmin A. Reyad; El‑Sayed Hemdan Eissa; Zulhisyam Abdul Kari; Moaheda E. H. Eissa; Saadiah Ibrahim; Saleha Khan; Mohammad Bodrul Munir; Abdelazeem M. Algammal; Ismail Youssef; et al. (Aquaculture International, 2025)

The effects of nano-selenium and/or vitamin C on the growth performance, blood health, organ histology, molecular alterations, and disease resistance of Nile tilapia (Oreochromis niloticus) against Saprolegnia ferax - Hayat Ali Alafari; Najah M. Albaqami; Yasmin M. Abd El-Aziz; Yasmin A. Reyad; El-Sayed Hemdan Eissa; Zulhisyam Abdul Kari; Moaheda E. H. Eissa; Saadiah Ibrahim; Saleha Khan; Mohammad Bodrul Munir; Abdelazeem M. Algammal; Ismail Youssef; et al. (Aquaculture International, 2025)

Dietary supplementation with fermented prebiotics and probiotics can increase growth, immunity, and histological alterations in Pacific whiteleg shrimp (Litopenaeus vannamei) challenged with Vibrio parahaemolyticus - El-Sayed Hemdan Eissa; Heba A. Dowidar; Nawal Al-Hoshani; Narjes Baazaoui; Naheda M. Alshammari; Safia M. A. Bahshwan; Zulhisyam Abdul Kari; Saadiah Ibrahim; Mohammad Bodrul Munir; Ammar AL-Farga; Moaheda E. H. Eissa; Yasmin M. Abd El-Aziz (Aquaculture International, 2025)

As nature's allies: Bee honey outperforms pomegranate and lemon juices in improving physio-biochemistry, antioxidants, RubisCO gene expression, and vase life of Calendula officinalis - Mostafa M. Rady; Marwa S.M. Habib; Ibrahim A.A. Mohamed; Hesham F. Alharby; Taia A.Abd El-Mageed; El‑Sayed M. Desoky; Alaa I.B. Abou-Sreea; Esmat F. Ali (South African Journal of Botany, 2024)

Aminophosphonate/sand nanocomposites for La(III) sorption: Application to REE concentrate - Ibrahim El-Tantawy El-Sayed; Xingmei Lu; Jiayu Xin; Azza A. Al-Ghamdi; Enas A. Imam; Hamada B. Hawash; Ahmed A. Galhoum; S. Wageh (Journal of Environmental Chemical Engineering, 2024)

Molecular mechanisms of extracellular-ATP-mediated colorectal cancer progression: Implication of purinergic receptors-mediated nucleocytoplasmic shuttling of HuR - Abdel-Aziz S. Shatat; Elsayed M. Mahgoup; Mohammed H. Rashed; Ibrahim G. Saleh; El-Sayed Akool (Purinergic Signalling, 2024)
One of the leading causes of cancer-related deaths worldwide is colorectal cancer (CRC). Extracellular ATP (e-ATP) and purinergic receptors (P2R) play a central role in CRC proliferation and progression. Human antigen R (HuR) is becoming more and more understood to be essential for the expression of genes linked to cancer. The current study demonstrates that ATP can mediate CRC (Caco-2 cells) progression via induction of HuR nucleocytoplasmic shuttling and subsequent expression of cancer-related genes, a consequence mostly mediated via the P2R receptor. It was also noted that suppression of HuR activity by using dihydrotanshinone I (DHTS) prevents cancer-related gene expression and subsequent CRC (Caco-2 cells) progression induced by ATP. The expression of cyclin A2/cyclin-dependent kinase 2 (CDK2), Bcl-2, ProT-α, hypoxia‐inducible factor1-α (HIF1-α), vascular endothelial growth factor A (VEGF-A), transforming growth factor-β (TGF-β) and matrix metallopeptidase 9 (MMP-9) induced by ATP were highly reduced in the presence of either PPADS (non-selective P2R antagonist) or DHTS. In addition, e-ATP-induced Caco-2 cell proliferation as well as cell survival were highly reduced in the presence of either PPADS or DHTS or selective CDK-2 inhibitor (Roscovitine) or selective Bcl-2 inhibitor (ABT-263). Furthermore, it was found that MMP-9 is critical for Caco-2 cells migration induced by e-ATP as demonstrated by a clear reduction in cells migration in the presence of a selective MMP-9 inhibitor (Marimastat). Collectively, these data demonstrate that ATP through P2R activation can induce HuR nucleocytoplasmic shuttling that could be translated into an increase in cancer-related genes expression and subsequent, cell proliferation and progression.

Compilation of secondary metabolites produced by fungal strains identified as Aspergillus flavus var. oryzae (formerly Aspergillus oryzae), with a review of biotechnological applications, and computational studies of their anti-COVID-19 activity - Sabrin R. M. Ibrahim; Flavia Pinzari; Shaimaa G. A. Mohamed; Hazem G. A. Hussein; Abdulrahim A. Alzain; Mohammed A. Almogaddam; Ahmed H. E. Hassan; Selwan M. El-Sayed; Nada A. S. O. AlGhamdi; Gamal A. Mohamed (Mycological Progress, 2024)

Retraction Note: The Protective Role of Toll-Like Receptor Agonist Monophosphoryl Lipid A against Vaccinated Murine Schistosomiasis - Ibrahim Aly; Essam H. Ibrahim; Rabab S. Hamad; Hoda E. L. Sayed; Sama M. N. Attiyah; Wafaa E-Komy; Hamed A. Ghramh; Ali Alshehri; Khalid M. Alsyaad; Mohammed Alshehri; Mona Kilany; Kareem Morsy; et al. (Acta Parasitologica, 2024)

6-Paradol exhibits antimicrobial, anti-quorum sensing and anti-virulence capacities on gram-negative bacteria: In vitro and in vivo studies - Hassan M. Okairy; Abdulrahman E. Koshak; Mahmoud A. Elfaky; Hossam M. Abdallah; Gamal A. Mohamed; Sabrin R.M. Ibrahim; Abdulrahim A. Alzain; El-Sayed Khafagy; Azza A.H. Rajab; Wael A.H. Hegazy (South African Journal of Botany, 2024)

Sorafenib and edaravone protect against renal fibrosis induced by unilateral ureteral obstruction via inhibition of oxidative stress, inflammation, and RIPK-3/MLKL pathway - Mohamed A. Abou Taha; Fares E.M. Ali; Ibrahim G. Saleh; El-Sayed Akool (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)
Renal fibrosis is the common endpoint of nearly all chronic and progressive nephropathies. Cell death and sterile inflammation are the main characteristics of renal fibrosis, which can lead to end-stage renal failure. The inflammatory reaction triggered by tissue damage is strongly related to necroptosis, a type of caspase-independent, regulated cell death. Using an animal model of unilateral ureteral obstruction (UUO), the anti-fibrotic effects of sorafenib (SOF), a multi-kinase inhibitor, and edaravone (EDV), a potent antioxidant and free radical scavenger, were examined in rats with obstructive nephropathy. Experimentally, animals were divided randomly into five groups: sham; UUO; UUO + SOF (5 mg/kg/day, P.O.); UUO + EDV (20 mg/kg/day, P.O.); and UUO + SOF + EDV groups. The kidney function biomarkers, oxidant/antioxidant status, renal mRNA expressions of TNF-α, collagen-1α, protein expressions of RIPK-1, RIPK-3, MLKL, caspase-8, HYP, MPO, and TNF-α were all significantly modulated by UUO. Administration of either SOF or EDV significantly attenuated cellular and molecular changes induced by UUO. Also, histopathological changes were improved. Moreover, SOF in combination with EDV, significantly improved UUO-induced renal fibrosis compared with each drug alone. Collectively, administration of either SOF or EDV or both of them significantly attenuated the rats with obstructive nephropathy, possibly by blocking the RIPK-3/MLKL necroptotic pathway and suppressing renal oxidative stress and inflammation.

Phytochemical profiling of Ananas comosus fruit via UPLC-MS and its anti-inflammatory and anti-arthritic activities: In Silico, In Vitro and In Vivo Approach - Sally E. Khaled; Faten Mohamed Ibrahim; Eman Abdelsalam; Kawkab A. Ahmed; Asmaa K. Al-Mokaddem; Wedian El Sayed Ashour; Amany A. Sleem; Reda Sayed Mohammed (Biocatalysis and Agricultural Biotechnology, 2024)

Potentiality of Melatonin for Reinforcing Salinity Tolerance in Sorghum Seedlings via Boosting Photosynthetic Pigments, Ionic and Osmotic Homeostasis and Reducing the Carbonyl/Oxidative Stress Markers - Nesma M. Helal; Hani S. Saudy; Maha M. A. Hamada; Ahmed Abou El-Yazied; Hany G. Abd El-Gawad; Soumya Mukherjee; Salem Mesfir Al-Qahtani; Nadi Awad Al-Harbi; Salwa M. El-Sayed; Mohamed F. M. Ibrahim (Journal of Soil Science and Plant Nutrition, 2024)
Salinity stress has become a major threat to worldwide crop production. Exogenous melatonin (MT) has appeared as a promising treatment against salt stress in several plant species. However, MT effect on the tolerance of sorghum plants under different saline conditions (moderate and severe) remains ambiguous. This study was carried out to explore the impact of MT (0, 50, 100 and 200 µM) as a foliar application on sorghum seedlings grown under moderate and severe saline conditions using sodium chloride, NaCl (75 and 150 µM NaCl). Salinity treatments were applied as solution in sand medium in pots. The results demonstrated that rising salinity level negatively affected plant growth, photosynthetic pigments (chlorophylls and carotenoids), leaf water status and ionic homeostasis (sodium, potassium, and calcium ions). Applied-MT specifically at 100 or 200 µM enhanced the osmotic balance, cell membrane stabilizing and leaf relative water content. These effects were associated with an obvious restriction to the level of hydrogen peroxide, lipid peroxidation (malondialdehyde content) and methylglyoxal. Moreover, antioxidant activities of peroxidase, catalase, superoxide dismutase, and ascorbate peroxidase enzymes were modulated by MT treatments. Molecular docking modeling assessment illustrated top-ranked confirmations between MT and the target antioxidant enzymes. MT forms multiple hydrogen bonds with key amino acid residues for glycine (A: 162), tryptophan (A: 41), leucine (A: 165), tyrosine (A: 235) in the active site of ascorbate peroxidase. The alkyl interactions with leucine (A: 37), arginine (A: 38) and cysteine (A: 168) also contribute to its high affinity. Despite sorghum plant is commonly moderately tolerant to salinity stress, the results of this study confirmed its high sensitivity to a wide range of saline conditions at early growth stages. Melatonin spraying led to improvements in various morphological, physiological and biochemical mechanisms that harmonized together to confer stress resistance to salt-stressed sorghum seedlings.

Thunbergia’s Flowers Secondary Metabolites a Natural Armor Against Kidney Damage by Diclofenac - Fatma Sayed Abdel-Aal Farag; Fatma Mohamed Abd El-Mordy; Mona H. Ibrahim; Enas S. Gad; Rania H. M. Soliman; Hend M. Anwar (Cell Biochemistry and Biophysics, 2024)

Facies hierarchy and microscopic features of upper Eocene rock succession, northern Eastern Desert, Egypt: inference on frequent subaerial exposure of Tethys platform and relevant palaeoclimates - Hanan S. Badawy; Soheir H. El-Shazly; Dina M. Sayed; Ibrahim M. Abd El-Gaied; Yasser F. Salama (Carbonates and Evaporites, 2024)

Chamomile Extract Reduces Cardiac Toxicity in Female Mice with Ehrlich Solid Carcinoma - Hamed A. Abosharaf; Amira M. Farag; Abdel Allem H. Abdel Allem; Ibrahim E. T. El-Sayed; Mohamed A. Akela; Ehab Tousson; Eman H. Kandil (Cell Biochemistry and Biophysics, 2024)

Sulfoxaflor residues and exposure risk assessment in grape under Egyptian field conditions - Farag Malhat; Anwar Hegazy; Dalia A. Barakat; El-Desoky Ibrahim; Mohamed Hussien; El-Sayed Saber; Ayman N. Saber (Environmental Science and Pollution Research, 2024)

Boosting Sinh Cosh Optimizer and arithmetic optimization algorithm for improved prediction of biological activities for indoloquinoline derivatives - Rehab Ali Ibrahim; Mohamed Aly Saad Aly; Yasmine S. Moemen; Ibrahim El Tantawy El Sayed; Mohamed Abd Elaziz; Hassan Ahmed Khalil (Chemosphere, 2024)

Impact of novel chloride-binding on strength, chloride penetration and resistance to corrosion of concrete exposed to chloride-bearing environment - Esraa S. Ibrahim; Mahmoud Gharieb; Mohamed R. Sakr; Hamdy A. El-Sayed; Mohamed O. R. El Hariri (Innovative Infrastructure Solutions, 2024)

Physicochemical, texture, microstructure, and antioxidant characteristics of karish cheese made from ultrasonic-treated skimmed buffalo milk - Aliaa Ali Darwish; Mahmoud Ibrahim El-Sayed; Wafaa Mahmoud Salama (International Dairy Journal, 2024)

Synthesis and molecular docking study of α-aminophosphonates as potential multi-targeting antibacterial agents - Rana R. Neiber; Nadia A. Samak; Jianmin Xing; Elshaymaa I. Elmongy; Ahmed A. Galhoum; Ibrahim El-Tantawy El Sayed; Eric Guibal; Jiayu Xin; Xingmei Lu (Journal of Hazardous Materials, 2024)

Ecological risk assessment of selected contaminants in seawater, sediment and some fish species from Alexandria beaches, South-Eastern Mediterranean Sea, Egypt - Safaa A. Abdel Ghani; Mohamed I.A. Ibrahim; Mohamed A. Shreadah; Abeer A.M. El-Sayed; Mohamed A. Aly-Eldeen (Environmental Nanotechnology, Monitoring & Management, 2023)

Automated diagnosis of EEG abnormalities with different classification techniques - Essam Abdellatef; Heba M. Emara; Mohamed R. Shoaib; Fatma E. Ibrahim; Mohamed Elwekeil; Walid El-Shafai; Taha E. Taha; Adel S. El-Fishawy; El-Sayed M. El-Rabaie; Ibrahim M. Eldokany; Fathi E. Abd El-Samie (Medical & Biological Engineering & Computing, 2023)

A hybrid deep learning model for rainfall in the wetlands of southern Iraq - Fehaid Alqahtani; Mostafa Abotaleb; Alhumaima Ali Subhi; El-Sayed M. El-Kenawy; Abdelaziz A. Abdelhamid; Khder Alakkari; Amr Badr; H. K. Al-Mahdawi; Abdelhameed Ibrahim; Ammar Kadi (Modeling Earth Systems and Environment, 2023)

Sponge-like zinc oxide nanoparticles loaded xanthan gum/cationic chitosan cryogel: Synthesis, characterization, microbicidal and adsorption of synthetic dye and heavy metal - Samar A. El-Kholy; Emad K. Radwan; Mehrez E. El-Naggar; Shaimaa T. El-Wakeel; Ibrahim El-Tantawy El Sayed (Journal of Environmental Chemical Engineering, 2023)

Electrospun TiO2-GO/PAN-CA nanofiber mats: A novel material for remediation of organic contaminants and nitrophenol reduction - Hassan M.A. Hassan; Ibrahim Hotan Alsohaimi; M.R. El-Aassar; Mohammed A. El-Hashemy; Mohamed Y. El-Sayed; N.F. Alotaibi; Mohamed A. Betiha; Mohammed Alsuhybani; Raghad Ayed Alenazi (Environmental Research, 2023)

Citrate-containing lemon juice, as an organic substitute for chemical citric acid, proactively improves photosynthesis, antioxidant capacity, and enzyme gene expression in cadmium-exposed Phaseolus vulgaris - Mostafa M. Rady; Hesham F. Alharby; El-Sayed M. Desoky; Ahmed R.M. Maray; Ibrahim A.A. Mohamed; Saad M. Howladar; Yasmine H. Abd Elmohsen; Ahmad Faraz; Shafaqat Ali; Abdelsattar AbdelKhalik (South African Journal of Botany, 2023)

Toxicity of mixture of polyethylene microplastics and Up Grade® pesticide on Oreochromis niloticus juvenile: I. Hemato-biochemical and histopathological alterations - Ibrahim A. Mohamed; Hamdy A.M. Soliman; Mervat Hana; Jae-Seong Lee; Alaa El-Din H. Sayed (Environmental Toxicology and Pharmacology, 2023)

Novel nanofiltration membrane modified by metal oxide nanocomposite for dyes removal from wastewater - Aya Abd El Aziz Elfiky; Mahmoud F. Mubarak; Mohamed Keshawy; Ibrahim El Tantawy El Sayed; Thanaa Abdel Moghny (Environment, Development and Sustainability, 2023)
This study focuses on the development of a nanocomposite membrane using polyvinyl chloride and nanocellulose@titanium aluminate to effectively filter and adsorb dye from wastewater. Various analytical techniques were used such as FTIR, XRD, SEM, and TGA to characterize the synthesized adsorptive nanocomposite membrane. The thermal and electrical properties of the membrane were measured using a static system. The study investigated the effect of different adsorbent dosages, pH levels, and dye concentrations on the membrane’s adsorption ability. The PVC-NC@TALCM nanocomposite membrane was found to remove 98.6% of MB dye when loaded with 5% titanium aluminate at pH 10. Kinetic and isotherm studies revealed that the adsorption of MB onto the membrane followed pseudo-second-order kinetics and Freundlich isotherms, respectively. The researchers also highlighted the economic and eco-friendly nature of the PVC-NC@TALCM nanocomposite membrane as a viable option for the removal of MB from industrial wastewater.

Removing of cationic dyes using self-cleaning membranes-based PVC/nano-cellulose combined with titanium aluminate - Aya Abd El Aziz Elfiky; Mahmoud F. Mubarak; Mohamed Keshawy; Ibrahim El Tantawy El Sayed; Thanaa Abdel Moghny (Environmental Science and Pollution Research, 2023)
This research used the phase inversion approach to construct polyvinyl chloride nanocellulose@titanium aluminate nanocomposite membranes (PVC/NC@TALCM) to adsorb and filter dye from wastewater. FTIR, XRD, and SEM were used to determine the adsorptive nanocomposite membrane that had been synthesized. The thermal and electrical properties measurements were carried out using a static system. The influence of several adsorbent dosages, pH, and dye concentrations on the nanocomposite membrane’s adsorption ability was investigated. Using a dead-end filtration system, the PVC-NC@TALCM was evaluated as a pressure filtration membrane system. It was found that 98.6% of MB dye was removed by PVC-NC@TALCM membrane, which was loaded with 5% titanium aluminate at pH 10. The kinetic adsorption studies indicated that the adsorption of MB onto the PVC-NC@TALCM nanocomposite membrane obeys pseudo-second-order that indicates the chemosorption process. The isotherm data were described using Freundlich and Langmuir models, and the Freundlich isotherms were shown to be more closely match the experimental data than the Langmuir model. Finally, the PVC-NC@TALCM nanocomposite membrane was economical, environmentally friendly, and self-cleaning.

Effect of mono- vs. bi-functionality of aminophosphonate derivatives on the enhancement of U(VI) sorption: physicochemical properties and sorption performance - Enas A. Imam; Ahmed I. Hashem; Ahmad A. Tolba; Mohammad G. Mahfouz; Ibrahim El-Tantawy El-Sayed; Ahmed I. El-Tantawy; Ahmed A. Galhoum; Eric Guibal (Journal of Environmental Chemical Engineering, 2023)

Highly efficient one-pot bioethanol production from corn stalk with biocompatible ionic liquids - Qingqing Zhu; Die Gao; Dongxia Yan; Jing Tang; Xiujie Cheng; Ibrahim El Tantawy El Sayed; Nour Sh. El-Gendy; Xingmei Lu; Jiayu Xin (Bioresource Technology Reports, 2023)

Immunostimulant potential of Moringa Oleifera leaves alcoholic extract versus Oregano Essential Oil (OEO) against cyclophosphamide-induced immunosuppression in broilers chicks - Mostafa Abdelgaber Mohamed; Amany Abdelbaky El-Mleeh; Rania Talat Hamad; Ibrahim Said Abu-Alya; Mohamed Hamdy El-Hewaity; Ahmed Ragab Elbestawy; Abdelrahman Mahmoud Elbagory; Ahmed Saber Sayed-Ahmed; Mabrouk Attia Abd Eldaim; Omnia Ibrahim Elshabrawy (Tropical Animal Health and Production, 2023)
The current study was conducted to evaluate the immunoenhancement effect of Moringa oleifera leaves alcoholic extract (MOLE) versus Oregano essential oil (OEO) against cyclophosphamide induced immunosuppression in broilers chicks. A total of a three hundred one-day-old chicks were assigned randomly into three main dietary groups, control, MOLE, and OEO for 14 days. After 14 days the three main experimental groups were subdivided into six groups, control, cyclophosphamide, MOLE, MOLE and Cyclophosphamide, OEO, and OEO and cyclophosphamide. Each group of these six groups was subdivided into three subgroups. Supplementation of broiler chicks with MOLE and OEO for 14 days significantly increased body weight compared to the control group. However, injection of broiler chicks with cyclophosphamide significantly induced body weight loss, impaired immunological response represented by decreasing total leukocytic count, differential leukocytic count, phagocytic activity, phagocytic index, and hemagglutinin inhibition titer for New Castle disease virus, lymphoid organs depletion, and increased the mortality rate. In contrast, supplementation of cyclophosphamide treated chicks with MOLE and OEO significantly reduced cyclophosphamide induced body weight loss and impaired immunological responses, as it showed significant increase in body weight, total leukocytic count, differential leukocytic count, phagocytic activity, phagocytic index, and hemagglutinin inhibition titer for New Castle disease virus, lymphoid organs proliferation, and reduced the mortality rate. This study indicated that MOLE and OEO supplementation ameliorated cyclophosphamide induced body weight loss and impaired immunological responses.

Bioremediation of chlorpyrifos residues using some indigenous species of bacteria and fungi in wastewater - Eman Mohammad Elzakey; Sabha Mahmoud El-Sabbagh; Eman El-Sayed Nour Eldeen; Ibrahim Abdel-Aziz Adss; Atef Mohamed Khedr Nassar (Environmental Monitoring and Assessment, 2023)
Pollutants cause a huge problem for humans, animals, plants, and various ecosystems, especially water resources. Agricultural, domestic, and industrial waste effluents change the water quality and affect living microorganisms. Therefore, the current study aimed to identify possible microorganisms in wastewater as potential bioremediation agents of pesticide residues. Wastewater samples were collected from El-Khairy agricultural drainage, which receives agricultural and domestic wastes. Bacteria and fungi species were isolated as clean cultures. Wastewater samples were analyzed for pesticide residues via gas chromatography-mass spectroscopy (GC–MS) system. Results uncovered the presence of ten pesticides ranging from 0.0817 to 28.162 µg/l, and the predominant pesticide was chlorpyrifos. Along with that, about nine species (3 bacterial and 6 fungal) were relatively efficient in the removal of chlorpyrifos residues up to 2000 µg/l with removal percentages ranging from 24.16 to 80.93% under laboratory conditions. Two bacterial isolates proficiently degraded significant amounts of chlorpyrifos: Bacillus cereus strain PC2 (GenBank accession No. MZ314010) and Streptomyces praecox strain SP1 (GenBank accession No. MZ314009). In-site bacterial and fungal isolates defined in the current study were proficient in cleaning wastewater of chlorpyrifos pesticide residues.

Synergistic effect of trans-zeatin and silymarin on mitigation of cadmium stress in chili pepper through modulating the activity of antioxidant enzymes and gene expressions - Mostafa M. Rady; Khalid S. Alshallash; El-Sayed M. Desoky; Hanan A.A. Taie; Ibrahim A.A. Mohamed; Ali M. El-Badri; Saad M. Howladar; Abdelsattar AbdelKhalik (Journal of Applied Research on Medicinal and Aromatic Plants, 2023)

Trimetazidine alleviates paclitaxel-induced peripheral neuropathy through modulation of TLR4/p38/NF-κB and klotho protein expression - Asmaa S.A. Hammad; Mohamed M. Sayed-Ahmed; Sara Mohamed Naguib Abdel Hafez; Ahmed R.N. Ibrahim; Mohamed M.A. Khalifa; Mahmoud El-Daly (Chemico-Biological Interactions, 2023)

Dietary Effects of Nano Curcumin on Growth Performances, Body Composition, Blood Parameters and Histopathological Alternation in Red Tilapia (Oreochromis sp.) Challenged with Aspergillus flavus - El-Sayed Hemdan Eissa; Bothaina A. Alaidaroos; Samyah D. Jastaniah; Mohammad Bodrul Munir; Manal E. Shafi; Yasmin M. Abd El-Aziz; Walaa K. Bazina; Saadiah binti Ibrahim; Moaheda E. H. Eissa; Marina Paolucci; Fatima S. Alaryani; Nadia N. B. Abd El-Hamed; et al. (Fishes, 2023)
This research examined the role of nano curcumin (NC) on growth performances, body composition, and blood parameters of red tilapia (Oreochromis sp.) challenged with Aspergillus flavus. Fish (5.0 g ± 0.30) were randomly distributed in four equal groups (20 fish per pond in triplicates) and fed various concentrations of NC fortified with 0 (Control), 40 mg/kg (NC1), 50 mg/kg (NC2), and 60 mg/kg diet (NC3) of nano curcumin. After eight weeks of the feeding trial, the fish were challenged with A. flavus for 15 days, and the cumulative mortality was recorded. Fish fed with different concentrations of NC improved significantly (p 0.05) difference between NC2 and NC3 treatments. However, NC3 exhibited higher performances. Fish feed supplemented with NC decreased the mortality rate when challenged with A. flavus. Hence, dietary supplementation of NC enhanced the growth and health status of Oreochromis sp. and protected it from A. flavus infection. This study suggests the optimum inclusion level of NC is a 50–60 mg/kg diet.

Design and cytotoxic evaluation via apoptotic and antiproliferative activity for novel 11(4-aminophenylamino)neocryptolepine on hepatocellular and colorectal cancer cells - Esraa Tariq Nagy; Abdullah A. S. Ahmed; Elshaymaa I. Elmongy; Saad M. EL-Gendy; Ibrahim Elmadbouh; Ibrahim El Tantawy El Sayed; Mabrouk Attia Abd Eldaim; Ahmed A. El-Gokha (Apoptosis, 2023)

Symbiosis of genus Hydractinia and in situ hermit crab in Kerunia cornuta Mayer-Eymar, 1899 from the Upper Eocene rocks in northwest Qarun Lake, Fayum area, Egypt - Dina M. Sayed; Soheir H. El-Shazly; Yasser F. Salama; Ibrahim M. Abd El-Gaied; Hanan S. Badawy (Journal of African Earth Sciences, 2023)

Ameliorative role of chitosan nanoparticles against silver nanoparticle-induced reproductive toxicity in male albino rats - Aya Abd Elhakeem Mahgoob; Ehab Tousson; Mabrouk Attia Abd Eldaim; Sami Ullah; Abdullah G. Al-Sehemi; Hamed Algarni; Ibrahim El Tantawy El Sayed (Environmental Science and Pollution Research, 2022)

Evaluation of energy extraction of PV systems affected by environmental factors under real outdoor conditions - Muhammed A. Hassan; Nadjem Bailek; Kada Bouchouicha; Abdelhameed Ibrahim; Basharat Jamil; Alban Kuriqi; Samuel Chukwujindu Nwokolo; El-Sayed M. El-kenawy (Theoretical and Applied Climatology, 2022)
The global agenda to increase the renewable energy share has driven many countries and entities to harness solar energy from solar photovoltaic (PV) systems. However, the power generation of PV systems is strongly affected by climate conditions. Therefore, the main objective of this study is to analyze and predict the power generation of different PV technologies under arid desert climate conditions on an hourly basis. Two areas have been considered as case studies: Adrar in Algeria and Alice Springs in Australia. A total of nine physical models and input parameter combinations from six different power plants have been used and tested for the suitability of the proposed models for predicting the power yield of PV power plants depending on solar irradiance and other meteorological variables. Then, an ensemble learning technique is applied to improve the performance capabilities of the best-fit input combinations. The results reveal that the global irradiance, ambient air temperature, and relative humidity combination are the most related to the PV power output of all technologies under all-sky conditions and provide effective and efficient performance with the proposed ensemble learning, with an estimated accuracy of over 99%.

Neuroprotective Potential of Intranasally Delivered Sulforaphane-Loaded Iron Oxide Nanoparticles Against Cisplatin-Induced Neurotoxicity - Ghadha Ibrahim Fouad; Sara A. M. El-Sayed; Mostafa Mabrouk; Kawkab A. Ahmed; Hanan H. Beherei (Neurotoxicity Research, 2022)
Cisplatin (CIS) is a platinum-based chemotherapeutic drug that is widely used to treat cancer. However, its therapeutic efficiency is limited due to its potential to provoke neurotoxicity. Sulforaphane (SF) is a natural phytochemical that demonstrated several protective activities. Iron oxide nanoparticles (Fe 3 O 4 -NPs) could be used as drug carriers. This study aimed to explore the nanotoxic influence of SF-loaded within Fe 3 O 4 -NPs (N.SF), and to compare the neuroprotective potential of both N.SF and SF against CIS-induced neurotoxicity. N.SF or SF was administrated intranasally for 5 days before and 3 days after a single dose of CIS (12 mg/kg/week, i.p.) on the 6 th day. Neuromuscular coordination was assessed using hanging wire and tail-flick tests. Acetylcholinesterase (AChE) activities and markers of oxidative stress were measured in the brain. In addition, the brain iron (Fe) content was estimated. CIS significantly induced a significant increase in AChE activities and lipid peroxides, and a significant decrement in glutathione (GSH) and nitric oxide (NO) contents. CIS elicited impaired neuromuscular function and thermal hyperalgesia. CIS-induced brains displayed a significant reduction in Fe content. Histopathological examination of different brain regions supported the biochemical and behavioral results. Contradict, treatment of CIS-rats with either N.SF or SF significantly decreased AChE activity, mitigated oxidative stress, and ameliorated the behavioral outcome. The histopathological features supported our results. Collectively, N.SF demonstrated superior neuroprotective activities on the behavioral, biochemical, and histopathological (striatum and cerebral cortex) aspects. N.SF could be regarded as a promising “pre-clinical” neuroprotective agent. Furthermore, this study confirmed the safe toxicological profile of Fe 3 O 4 -NPs.

Potential mechanisms underlying the association between type II diabetes mellitus and cognitive dysfunction in rats: a link between miRNA-21 and Resveratrol’s neuroprotective action - Norhan S. El-Sayed; Soha Elatrebi; Rasha Said; Heba F. Ibrahim; Eman M. Omar (Metabolic Brain Disease, 2022)
Cognitive impairment is considered as a typical feature of neurodegenerative diseases in diabetes mellitus (DM). However, the exact link between cognitive dysfunction and diabetes mellitus is still vague. This study aims to investigate some of the mechanisms underlying cognitive impairment that associates diabetes mellitus and insulin resistance. We investigated the role of resveratrol as well on cognitive function in experimentally induced type 2 diabetes highlighting on its influence on the expression of brain miRNA 21. Resveratrol is a naturally occurring, biologically active compound that has numerous significant impacts on the body. Type 2 diabetes mellitus was induced by high fat diet followed a single dose of streptozotocin. Diabetic rats were treated with resveratrol for four weeks. Rats were sacrificed after neurobehavioral testing. Hippocampal tissues were used to assess expression of miRNA 21, GSK and oxidative stress markers. Serum samples were obtained to determine glucose levels, lipid profile and insulin levels. Hippocampal and serum AGEs were measured as well and HOMA IR was calculated. We detected memory impairment and disturbed insulin signaling in diabetic rats. These derangements were reversed by resveratrol treatment partially due to increased expression of miRNA-21. Our study pins the role of miRNA-21 in modulating brain insulin signaling and hence alleviating cognitive dysfunction accompanying diabetes mellitus.

Hepatotoxic and Neurotoxic Potential of Iron Oxide Nanoparticles in Wistar Rats: a Biochemical and Ultrastructural Study - Mostafa Mabrouk; Ghadha Ibrahim Fouad; Sara A. M. El-Sayed; Maha Z. Rizk; Hanan H. Beherei (Biological Trace Element Research, 2022)

Ameliorating effects of probiotics on alterations in iron homeostasis and inflammation in COVID-19 - Eman M. El-Sayed; Khadiga S. Ibrahim (Molecular Biology Reports, 2022)

Retraction Note: Acaricidal and pathogenic effects of the entomopathogenic fungus Beauveria bassiana on engorged females of the fowl tick, Argas persicus (Argasidae) - Asmaa Ali Baioumy; Hamdy Hamed Swelim; Ahmed Adly Ibrahim; Fatma El‑Sayed Mohamed; Aleya Soliman Marzouk; Sherif Helmy El‑Alfy (Experimental and Applied Acarology, 2022)

“Anosmia” the mysterious collateral damage of COVID-19 - Abdulrahman K. Ahmed; Reem Sayad; Islam A. Mahmoud; Aya M. Abd EL-Monem; Salma H. Badry; Islam H. Ibrahim; Mahmoud HR Hafez; Mohamed A. El-Mokhtar; Ibrahim M. Sayed (Journal of NeuroVirology, 2022)

Sunshine duration measurements and predictions in Saharan Algeria region: an improved ensemble learning approach - El-Sayed M. El-kenawy; Abdelhameed Ibrahim; Nadjem Bailek; Kada Bouchouicha; Muhammed A. Hassan; Mehdi Jamei; Nadhir Al-Ansari (Theoretical and Applied Climatology, 2022)

Bioethanol production from defatted biomass of Nannochloropsis oculata microalgae grown under mixotrophic conditions - Nashwa A. H. Fetyan; Abo El-Khair B. El-Sayed; Fatma M. Ibrahim; Yasser A. Attia; Mahmoud W. Sadik (Environmental Science and Pollution Research, 2022)

Dietary conjugated linoleic acid and medium-chain triglycerides for obesity management - Khadiga S Ibrahim; Eman M El-Sayed (Journal of Biosciences, 2021)

RETRACTED ARTICLE: Acaricidal and pathogenic effects of the entomopathogenic fungus Beauveria bassiana on engorged females of the fowl tick, Argas persicus (Argasidae) - Asmaa Ali Baioumy; Hamdy Hamed Swelim; Ahmed Adly Ibrahim; Fatma El-Sayed Mohamed; Aleya Soliman Marzouk; Sherif Helmy El-Alfy (Experimental and Applied Acarology, 2021)

Grape seed extract ameliorated Ehrlich solid tumor-induced hepatic tissue and DNA damage with reduction of PCNA and P53 protein expression in mice - Mabrouk Attia Abd Eldaim; Ehab Tousson; Mohamed Mohamed Soliman; Ibrahim El Tantawy El Sayed; Abdel Aleem H. Abdel Aleem; Hebatalla Nashaat Elsharkawy (Environmental Science and Pollution Research, 2021)

The COVID-19 pandemic: prediction study based on machine learning models - Zohair Malki; El-Sayed Atlam; Ashraf Ewis; Guesh Dagnew; Osama A. Ghoneim; Abdallah A. Mohamed; Mohamed M. Abdel-Daim; Ibrahim Gad (Environmental Science and Pollution Research, 2021)

Risk assessment of horizontal curves using reliability analysis based on Google traffic data - Eman K. Ali; Ibrahim H. Hashim; Sayed A. Shwaly; Zaki M. Zidan; Sherif M. El-Badawy (Innovative Infrastructure Solutions, 2021)

Ameliorative effects of 9-diaminoacridine derivative against Ehrlich ascites carcinoma–induced hepatorenal injury in mice - Mabrouk Attia Abd Eldaim; Ehab Tousson; Ibrahim El Tantawy El Sayed; Asmaa Zakaria Abd Elmaksoud; Abdullah A. S. Ahmed (Environmental Science and Pollution Research, 2021)

Maternal Δ-aminolevulinic acid dehydratase 1-2 genotype enhances fetal lead exposure and increases the susceptibility to the development of cerebral palsy - Omaima Ibrahim Abdel Hamid; Eman El-Sayed Hassan Khayal; Sabry Abdel Rahman Tolba; Eman Elshahat Orabi (Environmental Science and Pollution Research, 2020)

Biosurfactant electrospun nanofibers exhibit minimal side effects on the structure and function of the liver tissue in male rat model - Hossam Abd Rabou Ebaid; Ahmed Abdel-Mageed; Jameel Homoud Al-Tamimi; Iftekhar Hassan; Ahmed Mostafa Rady; Mohamed Hassan El-Newehy; Ashraf Mohamed Mashaly; Ahmed AbdelFattah Mahmoud Abdel-Megeed; Ibrahim Alhazza; Essam Sayed Abdel-Halim; Abdelfattah Zeidan Mohamed Salem (Environmental Science and Pollution Research, 2020)

Optimization of Growth Conditions and Biochemical Composition of Microchloropsis salina, Cultured with Three Macroalgal Aqueous Extracts - Mohamed S. Abdel-Kareem; Soad M. Mohy El.Din; El-Sayed M. Ibrahim (Thalassas: An International Journal of Marine Sciences, 2020)

The Protective Role of Toll-Like Receptor Agonist Monophosphoryl Lipid A Against Vaccinated Murine Schistosomiasis - Ibrahim Aly; Essam H. Ibrahim; Rabab S. Hamad; Hoda E. L. Sayed; Sama M. N. Attiyah; Wafaa E-Komy; Hamed A. Ghramh; Ali Alshehri; Khalid M. Alsyaad; Mohammed Alshehri; Mona Kilany; Kareem Morsy; et al. (Acta Parasitologica, 2020)

Phenolic profiling and anti-Alzheimer’s evaluation of Eremobium aegyptiacum - Mona M. Marzouk; Lamyaa F. Ibrahim; Ali M. El-Hagrassi; Dalia B. Fayed; Ahmed Elkhateeb; El-Sayed S. Abdel-Hameed; Sameh R. Hussein (Advances in Traditional Medicine, 2020)

Utilization of Modified Attapulgite for the Removal of Sr(II), Co(II), and Ni(II) Ions from Multicomponent System, Part I: Kinetic Studies - Amira A. Mohammed; Ola A. Abdel Moamen; Sayed S. Metwally; Ahmed M. El-Kamash; Ibrahim Ashour; Mohammed S. Al-Geundi (Environmental Science and Pollution Research, 2020)

Beneficial Effects of Coconut Oil in Treatment of Parkinson’s Disease - K. S. Ibrahim; E. M. El-Sayed (Neurophysiology, 2020)

Correction to: Hemotoxic effects of some herbicides on juvenile of Nile tilapia Oreochromis niloticus - Mohamed Fathy; Ibrahim A. Mohamed; Ahmed I. A. Farghal; Sobhy A. H. Temerak; Alaa El-Din H. Sayed (Environmental Science and Pollution Research, 2020)

Hemotoxic effects of some herbicides on juvenile of Nile tilapia Oreochromis niloticus - Mohamed Fathy; Ibrahim A. Mohamed; Ahmed I. A. Farghal; Sobhy A. H. Temerak; Alaa El-Din H. Sayed (Environmental Science and Pollution Research, 2019)

Syntheses and in silico pharmacokinetic predictions of glycosylhydrazinyl-pyrazolo[1,5-c]pyrimidines and pyrazolo[1,5-c]triazolo[4,3-a]pyrimidines as anti-proliferative agents - Kamal F. M. Atta; Omaima O. M. Farahat; Tareq Q. Al-Shargabi; Mohamed G. Marei; Tamer M. Ibrahim; Adnan A. Bekhit; El Sayed H. El Ashry (Medicinal Chemistry Research, 2019)

Bio and phyto-chemical effect of Amphora coffeaeformis extract against hepatic injury induced by paracetamol in rats - Abo El-Khair B. El-Sayed; Wael M. Aboulthana; Amal M. El-Feky; Noha E. Ibrahim; Mohamed M. Seif (Molecular Biology Reports, 2018)

Teratogenic effects induced by chitosan oligosaccharide in Wistar female rat Rattus norvegicus - Amal Abdel Aziz Eisa; Gamal El-Sayed Aboelghar; Ibrahim Mahmoud Ammar; Hala Gabr Metwally; Samah Saied Arafa (Environmental Science and Pollution Research, 2018)

Assessment of Bioavailability of Some Heavy Metals to Wheat and Faba Bean in Sahl El-Tina, Egypt - A. M. Ali; S. M. Ibrahim; Y. A. Abd El-Hady; A. S. A. Sayed (Agricultural Research, 2018)

Synthesis and antimicrobial activity of newly synthesized 4-substituted-pyrazolo[3,4-d]pyrimidine derivatives - Ahmed M. El-Sayed; Samy M. Ibrahim; Mostafa K. Soltan; Mansour E. Abo-Kul (Medicinal Chemistry Research, 2017)

The effectiveness of dietary sunflower meal and exogenous enzyme on growth, digestive enzymes, carcass traits, and blood chemistry of broilers - Mahmoud Alagawany; Adel I. Attia; Zenat A. Ibrahim; Reda A. Mahmoud; Sabry A. El-Sayed (Environmental Science and Pollution Research, 2017)

Effect of the types of dietary fats and non-dietary oils on bone metabolism - Eman El-Sayed; Khadiga Ibrahim (Critical Reviews in Food Science and Nutrition, 2017)

Nephroprotective efficacy of ceftriaxone against cisplatin-induced subchronic renal fibrosis in rats - Mohamed M. Abdel-Daim; Yasser S. El-Sayed; Mabrouk Abd Eldaim; Abdelazim Ibrahim (Naunyn-Schmiedeberg's Archives of Pharmacology, 2017)

Animal level risk factors associated with Babesia and Theileria infections in cattle in Egypt - Mohamed Abdo Rizk; Akram Salama; Shimaa Abd-El-Salam El-Sayed; Ahmed Elsify; Maged El-ashkar; Hussam Ibrahim; Mohamed Youssef; Sabry El-Khodery (Acta Parasitologica, 2017)
In present study, blood samples were collected randomly from 439 cows at three main regions of Egypt (northern, central and southern). Molecular diagnosis of

Influence of environmental parameters on toxic cyanobacterial bloom occurrence in a Lake of Bangladesh - Md. Abu Affan; Hussein El-Sayed Touliabah; Salim Marzoog Al-Harbi; Najah Ibrahim Abdulwassi; Adnan Jaman Turki; Md. Mahfuzul Haque; Saleha Khan; Randa Ahmed Elbassat (Rendiconti Lincei. Scienze Fisiche e Naturali, 2016)

Synthesis and in vitro cancer cell growth inhibition evaluation of 11-amino-modified 5-Me-indolo[2,3-b]quinolines and their COMPARE analyses - Masashi Okada; Zhen-Wu Mei; Md. Imran Hossain; Li Wang; Taihei Tominaga; Takeshi Takebayashi; Masaharu Murakami; Mizuki Yasuda; Tsukasa Shigehiro; Tomonari Kasai; Akifumi Mizutani; Hiroshi Murakami; et al. (Medicinal Chemistry Research, 2016)

Hydrocarbon probability of Middle Ordovician Hawaz Formation, Murzuq Basin, Southwestern Libya - El Sayed Ibrahim Selim; Adel Kamel; Adel Kashlaf (Arabian Journal of Geosciences, 2015)

Transition metal complexes of α-aminophosphonates Part I: synthesis, spectroscopic characterization, and in vitro anticancer activity of copper(II) complexes of α-aminophosphonates - Hanaa Abdel Latif El-Boraey; Ahmed Abdel Aleem El-Gokha; Ibrahim El Tantawy El-Sayed; Mariam Ahmed Azzam (Medicinal Chemistry Research, 2015)

Application of spectral analysis technique on ground magnetic data to calculate the Curie depth point of the eastern shore of the Gulf of Suez, Egypt - El Sayed Ibrahim Selim; Essam Aboud (Arabian Journal of Geosciences, 2014)

Cyclooxygenase-2 single-nucleotide polymorphisms and hepatocellular carcinoma in Egypt - Faten Zahran Mohamed; Yousry Mostafa Hussein; Ibrahim Mohey El-Deen; Marwa Sayed Sabea (Molecular Biology Reports, 2014)

In vitro antiproliferative activity of 11-aminoalkylamino-substituted 5H-indolo[2,3-b]quinolines; improving activity of neocryptolepines by installation of ester substituent - Wen-Jie Lu; Marta Świtalska; Li Wang; Mizuki Yonezawa; Ibrahim El-Tantawy El-Sayed; Joanna Wietrzyk; Tsutomu Inokuchi (Medicinal Chemistry Research, 2013)

Synthesis, molecular modeling study, preliminary antibacterial, and antitumor evaluation of N-substituted naphthalimides and their structural analogues - Adel S. El-Azab; Amer M. Alanazi; Naglaa I. Abdel-Aziz; Ibrahim A. Al-Suwaidan; Magda A. A. El-Sayed; Magda A. El-Sherbeny; Alaa A.-M. Abdel-Aziz (Medicinal Chemistry Research, 2013)

A new isoflavone from Blepharis ciliaris of an Egyptian origin - Mohamed A. El-Shanawany; Hanaa M. Sayed; Sabrin R. M. Ibrahim; Marwa A. A. Fayed; Mohamed M. Radwan; Samir A. Ross (Medicinal Chemistry Research, 2013)

Neocryptolepine analogues containing N-substituted side-chains at C-11: synthesis and antischistosomicidal activity - Ibrahim El Sayed; Fatem Ramzy; Samia William; Mohamed El Bahanasawy; Mostafa M. Abd El-Sattar (Medicinal Chemistry Research, 2012)

Inhibition of endogenous CO by ZnPP protects against stress-induced gastric lesion in adult male albino rats - Ibrahim Ibrahim; Salah El-Sayed; Selim Abdel-Hakim; Magdy Hassan; Neven Aziz (Journal of Physiology and Biochemistry, 2012)

The use of seismic interpretation for delineating the characteristic features of Messinian channels in the north Nile Delta, Egypt - El Sayed Ibrahim Selim (Arabian Journal of Geosciences, 2012)

Characteristic features of salt tectonics offshore North Sinai, Egypt - El Sayed Ibrahim Selim; Mohamed A. Omran (Arabian Journal of Geosciences, 2012)

Potential anti-inflammatory activity and ulcerogenicity study of some novel pyrimido[4′,5′:4,5]pyrimido[1,6-a]azepine derivatives - Nehad A. El-Sayed; Fadi M. Awadallah; Nashwa A. Ibrahim; Mohamed T. El-Saadi (Medicinal Chemistry Research, 2012)

Antihypercholesterolaemic effect of ginger rhizome (Zingiber officinale) in rats - El-Sayed M. ElRokh; Nemat A. Z. Yassin; Siham M. A. El-Shenawy; Bassant M. M. Ibrahim (Inflammopharmacology, 2010)

Shelf Sediments of Alexandria Region, Egypt: Explorations and Evaluation of Offshore Sand Sources for Beach Nourishment and Transport Dispersion - Omran E. Frihy; Ebtessam E. El Sayed; Essam A. Deabes; Ibrahim H. Gamai (Marine Georesources & Geotechnology, 2010)

Characterization of NS3 protease from an Egyptian HCV genotype 4a isolate - Mahmoud Mohamed Bahgat; Ahmed Atef Ibrahim; Dina Nadeem Abd-Elshafy; Ahmed Atef Mesalam; Hossam Eid Gewaid; Amany Abd-Elghany Ismaeil; Ahmed Mohamed El-Waseef; Amany Sayed Maghraby; Ahmed Barakat Barakat; Mohamed Abd-Elhafez El-Far; Hossam El-Din Ahmed Ghanem; Amro Mahmoud Mohamed; et al. (Archives of Virology, 2009)

Design, synthesis, and in vitro evaluation of cytotoxic activity of new substituted 1,4-benzoquinones and hydroquinones - Ibrahim Chaaban; El-Sayeda EL-Khawass; Mona Mahran; Ola El-Sayed; Hassan El-Saidi; Hassan Aboul-Enen (Medicinal Chemistry Research, 2007)